Solar Powered Water Tank Level Monitoring System with IoT - Hasanal, Mohd Azamuddin; Che Soh, Mohd Jais (Evolution in Electrical and Electronic Engineering, 2024)
This project gives us an insight into the use and monitoring of water through the application of a water level monitoring system. This thesis outlines a monitoring system that uses IoT technology and is powered by solar energy. Inadequate water supply is a source of constraints for the smooth running of an industry as well as work at home. This is addressed with an innovative approach that aims to improve water tank level monitoring capabilities by integrating solar energy. The system uses an ultrasonic sensor placed on top of the water tank to consistently monitor the water level and deliver real-time data to the microcontroller unit. This system is equipped with solar panels, ensuring continuous power supply and not producing environmental pollution, also promoting a system with better green energy. It may be possible to improve communication by utilizing Internet of Things (IoT) technology. Wireless communication is used by the system to provide smooth data flow between microcontrollers, sensors, and users. The user’s mobile device may show sensor data thanks to the Wi-Fi module, which also makes it easier for the user and the system to connect. A visual depiction of water levels is another feature that user-friendly online interfaces, like the Blynk application, offer to its customers. This enables consumers to decide quickly by using the information on display to guide their choices.